Mo-Doped Zn, Co Zeolitic Imidazolate Framework-Derived Co9S8 Quantum Dots and MoS2 Embedded in Three-Dimensional Nitrogen-Doped Carbon Nanoflake Arrays as an Efficient Trifunctional Electrocatalysts for the Oxygen Reduction Reaction, Oxygen Evolution Reaction, and Hydrogen Evolution Reaction - Zhang, Wenming; Zhao, Xinyan; Zhao, Youwei; Zhang, Jiaqing; Li, Xiaoting; Fang, Lide; Li, Ling (ACS applied materials & interfaces, 2020)
Herein, we first propose a facile strategy to synthesize Co9S8 and MoS2 nanocrystals embedded in porous carbon nanoflake arrays supported on carbon nanofibers (Co9S8-MoS2/N-CNAs@CNFs) by the pyrolysis of Mo-doped Zn, Co zeolitic imidazolate framework grown on carbon nanofibers and subsequent sulfuration. The electrocatalyst shows high and stable electrocatalytic performance, with a half-wave potential of 0.82 V for oxygen reduction reaction and an overpotential at 10 mA cm–2 for oxygen evolution reaction (0.34 V) and hydrogen evolution reaction (0.163 V), which outperform the metal–organic framework-derived transition metal sulfide catalysts reported so far. Furthermore, the Co9S8-MoS2@N-CNAs@CNFs are employed as an air cathode in a liquid-state and all-solid-state zinc-air battery, presenting high power densities of 222 and 96 mW cm–2, respectively. Such excellent catalytic activities are mainly owing to the unique three-dimensional structure and chemical compositions, optimal electronic conductivity, adequate surface area, and the abundance of active sites. Thus, this work provides an important method for designing other metal–organic framework-derived three-dimensional structural sulfide quantum dot multifunctional electrocatalysts for wider application in highly efficient catalysis and energy storage.